Polyphenolic Composition and Antimicrobial, Antioxidant, Anti-Inflammatory, and Antihyperglycemic Activity of Different Extracts of Teucrium montanum from Ozren Mountain - Pero Sailović; Božana Odžaković; Darko Bodroža; Jelena Vulić; Jasna Čanadanović-Brunet; Jelena Zvezdanović; Bojana Danilović (MDPI AG, 2024)
Teucrium montanum has widespread use in folk medicine on the Balkan peninsula. In order to scientifically justify this use, the composition and biological activity of aqueous, ethanol, and acetone extract were investigated in this study. Moreover, acetone and ethanol extracts were obtained from the plant material previously exhausted by water extraction. A total of 27 compounds were detected in extracts by UHPLC-DAD-MS/MS analysis, with all of them present in acetone and ethanol extracts. Consequentially, the acetone and ethanol extracts showed higher contents of total phenols of 23% and 18%, respectively, compared to the water extract. The results indicated high biological potential in the investigated extracts. Among all extracts, the aqueous extract showed slightly higher antimicrobial potential, especially against Gram-positive strains, probably due to the release of components soluble in water from the dry unexhausted plant material. On the other hand, the acetone and ethanol extracts had significantly higher antioxidative (by 20%), anti-inflammatory activity (up to 3 and 4 times higher, respectively), and α-glucosidase inhibitory potential (3 times higher) than the aqueous extract. The results of this investigation reveal the great potential of the use of T. montanum in various branches of food, cosmetics, and the pharmaceutical industry. An important part of this research is a confirmation that, once exhausted by water extraction, for example by hydrodistillation, T. montanum plant material can be reused for obtaining valuable products with a wide range of biological activities.